Hubungan Pola Asuh Orang Tua, Lingkungan Dan Pendidikan Terhadap Kemandirian Anak Di SDN Lanbau 01 - Annisa Alfina Andriyani; Solehudin Solehudin; Adi Wijaya (Pusat riset dan Inovasi Nasional, 2024)
A thesis is an important element in the higher education process, which is also proof of a student's integrity in applying the knowledge gained during their studies. However, the process of preparing a thesis is often faced with various problems, especially by final year students who experience high levels of anxiety. Independence is an attitude of being able to stand alone without depending on the people around him, especially parents, being able to choose and determine his own choices according to what he wants.The aim of this research is to determine the relationship between parenting styles, environment and education on children's independence at SDN Lanbau 01. The research method used by researchers is a correlational analytical research method with a cross sectional design. The data collection method involves using the Vineland Social Maturity Scale (VSMS) questionnaire to determine parental parenting patterns, environmental modification questionnaire, education level questionnaire, Parenting Style and Dimension Question (PSDQ). The results of this research obtained a P-value of 0.010, which means sig 0.010 0.05, so there is a correlation or relationship between parenting patterns and independence. Independence. If the P-value is 0.000, which means the sig value is 0.000 0.05, then there is a correlation or relationship between education and children's independence at SDN Lanbau 01. Based on the results of the analysis, parenting patterns, environment and education are related to children's independence at SDN Lanbau 01